Self-employment and eudaimonic well-being: Energized by meaning, enabled by societal legitimacy - Stephan, U.; Tavares, S. M.; Carvalho, H.; Ramalho, J. J. S.; Santos, S. C.; van Veldhoven, M. (Journal of Business Venturing, 2020)
This study investigates why and where self-employment is related to higher levels of eudaimonic well-being. We focus on meaningfulness as an important eudaimonic process and subjective vitality as a eudaimonic well-being outcome that is central to entrepreneurs' proactivity. Building on self-determination theory, we posit that self-employment, relative to wage-employment, is a more self-determined and volitional career choice, which enhances the experience of meaningfulness at work and perceptions of work autonomy. In a multi-level study of 22,002 individuals and 16 European countries, meaningfulness at work mediates the relationship between self-employment and subjective vitality and explains this relationship better than work autonomy. We identify moderating effects of context: the societal legitimacy of entrepreneurship in a country affects the choice set of alternative career options that individuals can consider and thus shapes the experience of meaningfulness at work and work autonomy, and thereby indirectly subjective vitality. These findings expand our understanding of eudaimonic well-being, entrepreneurs' work, and the role of context in entrepreneurship and well-being research. They complement existing research on hedonic well-being of entrepreneurs and extend the scarce literature on their eudaimonic well-being.